CURRENT EVIDENCE OF TREATMENT WITH TUMOR TREATING FIELDS (TTF) IN PATIENTS WITH GLIOBLASTOMA AS A FOURTH MODALITY TREATMENT OPTION - Bojovska-Trajanovska Valentina; Stojkovski Igor; Ivanova Maja; Djundeva, Jasmina; Petkovska Gordana (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University Skopje, R.N.Macedonia, 2022)
Background: High-grade glial tumors (HGGTs) are the most common malignant tumors that occur in the central nervous system; they form about 40% of all primary brain tumors. The group of high-grade glial tumors includes: Anaplastic astrocytoma (AA), Anaplastic Oligodendroglioma (AO) as well as Glioblastoma (GBM). Tumor Treating Fields (TTFs) itself is a completely non-invasive and innovative approach, and because of the specific frequency which it uses, it has a selective anticancer or antimitotic effect on malignant cells. Methods: A systematic search was conducted in PubMed in database and the most relevant articles were selected which are forming scientific evidence for application of this type of treatment in clinical setting. Results: In the absence of meta-analysis, the most relevant articles were selected and a combination of evidence has been extracted to systematically organize this article. Positive studies with clinical benefits have been selected for further analysis. Conclusion: As a result of several clinical and preclinical researches, the inclusion of the TTF (Tumor Treating Fields) treatment modality to the earlier traditional three modality treatment for patients with glioblastoma multiforme, is considered to become a standardized treatment, i.e., according to the novel approach, four modalities are used for newly diagnosed or recurrent patients with GBM modality treatment, i.e., cocktail-based therapy. And it’s considered a valuable option for this type of solid tumors, so-called “cold” tumors.
Keywords: Tumor-Treating Fields; glioblastoma; systematic review